B cell depletion skews cd4+ t cell towards a pro-inflammatory phenotype in aged atherosclerotic mice. (10th June 2022) - De Mol, J; Postel, R; Smit, V; Bernabe Kleijn, MNA; Bot, I; Kuiper, J; Foks, AC
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Dutch Heart Foundation ERA CVD Aims: Aging is associated with changes in the composition and function of the immune system, such as decreased B cell numbers and reduced antibody responses (1). In addition, aging is related to an increased incidence of inflammatory diseases, such as the lipid-driven chronic inflammatory disease atherosclerosis, the main underlying cause of cardiovascular disease (2). B cells play a major role in atherosclerosis progression by antibody secretion, antigen presentation and T cell regulation. Different B cell subsets, with either proatherogenic or antiatherogenic properties, have been identified in atherosclerosis, but the impact of aging on B cells during atherosclerosis remains to be elucidated. In contrast to young atherosclerotic mice where few B cells are found within the plaque, single cell RNA sequencing and flow cytometry data from our group revealed that B cells are one of the most dominant leukocytes present in atherosclerotic aortas from naturally aged LDLr-/- mice. In this study, we aimed to gain further insights into the role of these aged B cells on T cell immunity in atherosclerosis by depleting B cells in aged atherosclerotic mice. Methods and Results: Aged (85-95 weeks) atherosclerotic male LDLr-/- mice were kept on a chow diet for six weeks, during which the mice received 250 µg B cell-depleting anti-CD20 antibody (Genentech) (n=12) or 250 µg rat IgG2a isotype control (n=12) once a week intraperitoneally. Mice that received the anti-CD20 antibody showed effective B cell depletion in the blood and lymphoid organs, such as the spleen and lymph nodes, but also locally in the atherosclerotic plaque. In addition, B cell depleted mice showed a significant increase in the percentage of T-bet expressing CD4+ T cells in aortic plaques compared to control mice (αCD20: 25.05±2.88% vs. ctrl: 15.94±2.14%, p<0.05). Furthermore, the percentage of RORyt+ and IL-17+ CD4+ T cells in the spleen and heart draining lymph nodes was increased after B cell depletion, indicating a shift towards Th17 differentiation. Conclusions: Collectively, we show that CD20+ B cell depletion in aged LDLr-/- mice skews CD4+ T cells towards a Th1 phenotype in the atherosclerotic plaque and towards a Th17 phenotype in lymphoid organs, suggesting a protective role for aged B cells in atherosclerosis. However, B cells are a heterogeneous population and further research should elucidate whether aged B cells exert a pro- or anti-atherogenic role. In conclusion, our results indicate that aged B cells have an important function in CD4+ T cell differentiation and could be attractive targets to combat age-related cardiovascular disease.